EFFECT OF ADDING POWDER CUMIN (Cuminum cyminum) AND THYME (Thymus vulgaris) AND THEIR MIXTURE TO BROILER DIETS ON SOME BLOOD PARAMETERS AND PRODUCTIVE TRAITS. - Ali, Nashwan Majid; Rebh, Ahmed Yasir (Diyala Agricultural Sciences Journal, 2020)
The study was conducted at the determine the effect of adding a synergistic mixture of cumin and thymus powder in broiler diets and to determine their effects on some blood parameters and production performance of the broiler. 240 day old broiler chicks Ross-308 were divided randomly into 4 groups of 60 chicks of each treatments. Chicks of each treatment were also divided into 3 replicate of 20 chicks. The treatments were divided into (T1) on a regular diet without any addition, the (T2) Was fed on a regular diet added to it (T3) fed on the same diet plus 1g per kg of thyme feed, (T4) fed on the same diet plus 1g cumin +1 g thymus per kg of feed, blood extraction during the experiment period and at the age of 3 weeks and 6 week. The production characteristics are calculated weekly until the age of marketing . The results showed a significant improvement (P<0.01) in the productivity traits, which included body weight and feed consumption, and ranged between P<0.05 and P (0.05) in the weight increase and food conversion coefficient. The characteristics of blood the same direction by improving the and high of the glucose and protein levels, as well as continuing improvement in the experimental factors for the activity of the enzymes of the liver under study, which included ALP, AST and ALT. Therefore it can be concluded that the addition of these medicinal herbs alone or Chicken meat has led to a clear improvement in most of the productive and biochemical traits, and thus it can be introduced as one of the important food additives to improve the productive and physiological performance of birds.